PENERAPAN METODE SIMPLE ADDITIVE WEIGHT UNTUK FAKTOR PENENTU KUALITAS KAIN DEPARTEMEN LABORATORIUM - Febia Nurfitriani; Falentino Sembiring (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
In the garment industry, Quality Control Laboratory is one of the main elements in carrying out industrial processes. The purpose of the quality control laboratory is so that there is no second quality in goods so that they can be controlled, get quality values, selected so that consumers feel satisfied and the company does not suffer losses. In the process of selecting fabrics in this laboratory department, research is needed so that the process can be completed quickly and accurately. However, there are problems that occur in the process. Sometimes the quality control department of this department still finds it difficult to determine the priority of the influential fabric workmanship standards to be produced in accordance with the buyer's standards. Therefore, this research requires a decision support system by choosing the Simple Additive Weight method. This method can make it easier for laboratory department workers to choose which process should take precedence. Determination of the selection of fabric work is determined by the existence of alternative options based on criteria from the data of the fabric model to be made for the selection of fabric work. The results of this study were able to determine a value from the weight of each criterion and an assessment to find the weight of each criterion and then rank and obtain alternatives. This decision support system is able to facilitate the workers in the laboratory department of PT. Busana Indah Global. Keywords: Quality Control, Laboratory, Simple Additive Weight